Gender Differences in Verbal Fluency and Language Dominance by Arab Students - DARIN NSHIWI; FAILASOFAH FAILASOFAH (Indonesian Research Journal in Education |IRJE|, 2019)
This study falls within Multi-lingual Processing area. The aim of this study is to investigate the language dominance and gender differences in verbal fluency by Arab students in a foreign country. The impact of duration residence's years and the differences in the phonological and semantic fluency by gender in English as a foreign language, Standard Arabic and Arabic dialect among Arab students at Pannonia University in Hungary are examined. Ten Arab students were involved in this study (five males and five females) between the ages of 25-35 years old. The task in this study contained two main categories to measure the phonological and semantic fluency. The participants were asked to write as many words as they could that started with letter (S) in one minute in the phonological category. While in the semantic category, they were required to write as many jobs as they could in English, Standard Arabic and Arabic dialect. This study concludes that the phonological fluency in English and Arabic dialect is higher than in Standard Arabic. However, the semantic fluency in Standard Arabic and Arabic dialect is higher than English because vocabulary in both categories are almost the same. It is also found that female participants are more fluent in the phonological and semantic categories. Nevertheless, there are no real differences in processing the phonological and semantic tasks according to gender among educated Arab students residing in a foreign country.